Beta-Cell-Derived Extracellular Vesicles: Mediators of Intercellular Communication in the Islet Microenvironment in Type 1 Diabetes - Mette C. Dekkers; Xudong Pu; Agustin Enciso-Martinez; Arnaud Zaldumbide (Cells)
Type 1 diabetes (T1D) is a chronic autoimmune disorder characterised by an autoimmune response specifically mounted against the insulin-producing beta cells. Within the islet, high cellular connectivity and extensive vascularisation facilitate intra-islet communication and direct crosstalk with the surrounding tissues and the immune system. During the development of T1D, cytokines and extracellular vesicles released by beta cells can contribute to the recruitment of immune cells, further amplifying autoimmunity and aggravating beta cell damage and dysfunction. In this review, we will evaluate the role of beta-cell-derived extracellular vesicles as mediators of the autoimmune response and discuss their potential for early diagnosis and new therapeutic strategies in T1D.